Numerical Investigation of Flow Control Via Blowing And Suction on NACA4415 Airfoil - AMRANI, Djedjiga; IMINE, Bachir; ADJLOUT, Lahouari; MEFTAH, Sidi Mohammed ElAmine (University of Eloued جامعة الوادي, 2018)
a blowing flow control method was studied in the present work around an asymmetrical NACA 4415 profile. The effect of many parameters are investigated (jet angle (0°, 30°and 45°), jet amplitude (A= 0.1 to 1)), combinations of two actuators jet and an effect of suction was compared to the blowing. Flow was fully turbulent for Reynolds numbers of 2.18x105. A commercial code, fluent was used in the current simulations. The turbulence model used is SPALLART ALLMARAS. The results show that the lift coefficient increases and drag coefficient decreases while the amplitude rose. The optimum location of jet is near to the stall position (30% c) and a tangential jet is more beneficial. The maximum lift coefficient increases by 13 % and a flow separation is delayed to 17°for the dual jet who seems to be the best.
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: flow control, blowing, suction, lift, drag, stall, CFD.